Birokrasi, Kekuasaan dan Bisnis - Nuraini, Hikmah (Universitas Serang Raya, 2017)
Bureaucracy as an instrument of administrative processes in the process of policy implementation. Strategic existence in the governance process, making it a class of its own, so there are some assumptions that the bureaucracy can build their own interests. Bureaucracy always have their own interests. Although there are indeed some influential institutions around. However, its existence as a class of its own making for a more participatory in the policymaking process. Bureaucracy as the frontline in the implementation of governance required for professional and not co-opted by political interests so that he can show that the ideal posture in the public expected. Progress of a nation one of which is determined by the ability of the bureaucratic apparatus in carrying out its duties and functions, namely, as a public servant to the community in a professional and accountable. If the public can be served well by the bureaucratic apparatus, the apparatus itself bureaucracy was able to put the position and his position as a civil servant